Participation of farmers in market value chains: A tailored Antràs and Chor positioning indicator - Tulia Gattone (Bio-based and Applied Economics (BAE), 2024)
This study presents a micro-level indicator of farmers' positioning in the market chain, based on the conceptual framework outlined by Antràs and Chor (2013, 2018). The indicator considers the selling location of a farming household and its crop buyers. Using panel data from the World Bank's 'Living Standards Measurement Study: Integrated Surveys on Agriculture' for Ethiopia and Nigeria, this paper applies the proposed indicator empirically and showcases its superior performance in comparison to existing alternatives at the micro-level. Furthermore, by analyzing the dynamics of farmers' food and total consumption over time and controlling for various household and production characteristics, as well as potential confounding factors, this study shows that moving towards a downstream position in the market chain has a positive impact on farmers' food and total consumption levels. The results are validated through sensitivity analysis and robustness checks.
Keywords: Q12; O12; O13; C23; 330; value chains; economic development; market chain; farming households